Direct, digital & data-driven marketing - Spiller, Lisa (New Delhi, sage, 2020)
"In this latest edition of her classic text, Lisa Spiller takes an insightful, in-depth look at contemporary marketing concepts, tactics, and techniques and the dynamic innovations that continue to drive and shape this multi-faceted, multi-dimensional field"--
Keywords: Direct marketing; Internet marketing; Marketing -- Data processing